Community Attitudes Towards Preserving Nandong Art in Gampong Sambay, Teluk Dalam District, Simuelue Regency - Andi Fadinul (Arkus, 2020)
Nandong is one of the cultures in Simeulue Regency, where this culture is in the form of rhymes or poems accompanied by drums and violins and played by men. Nandong culture or art is usually held on certain occasions, such as weddings and circumcision, but it is also displayed when no certain events occur. In a wedding or circumcision, usually, the host or the person who organizes the event deliberately invites groups or people proficient in performing Nandong to be held at the venue. However, the preservation of Nandong culture seems to be fading due to the development of modern musical instruments so that local culture is rarely displayed. This study aims to explore the attitudes and behavior of the people in Gampong Sambay towards Nandong arts.